Identification of microRNAs Involved in Regeneration of the Secondary Vascular System in Populus tomentosa Carr - Tang, Fang; Wei, Hairong; Zhao, Shutang; Wang, Lijuan; Zheng, Huanquan; Lu, Mengzhu (Frontiers in Plant Science, 2016)
Wood formation is a complex developmental process primarily controlled by a regulatory transcription network. MicroRNAs (miRNAs) can modulate the expression of target genes involved in plant growth and development by inducing mRNA degradation and translational repression. In this study, we used a model of secondary vascular system regeneration established in Populus tomentosa to harvest differentiating xylem tissues over time for high-throughput sequencing of small RNAs. Analysis of the sequencing data identified 209 known and 187 novel miRNAs during this regeneration process. Degradome sequencing analysis was then performed, revealing 157 and 75 genes targeted by 21 known and 30 novel miRNA families, respectively. Gene ontology enrichment of these target genes revealed that the targets of 15 miRNAs were enriched in the auxin signaling pathway, cell differentiation, meristem development and pattern specification process. The major biological events during regeneration of the secondary vascular system included the sequential stages of vascular cambium initiation, formation, and differentiation stages in sequence. This study provides the basis for further analysis of these miRNAs to gain greater insight into their regulatory roles in wood development in trees.